2020
DOI: 10.1038/s41598-020-59047-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying residue-specific conformational dynamics of a highly reactive 29-mer peptide

Abstract: Understanding structural transitions within macromolecules remains an important challenge in biochemistry, with important implications for drug development and medicine. insight into molecular behavior often requires residue-specific dynamics measurement at micromolar concentrations. We studied MP01-Gen4, a library peptide selected to rapidly undergo bioconjugation, by using electron paramagnetic resonance (epR) to measure conformational dynamics. We mapped the dynamics of MP01-Gen4 with residue-specificity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…LLPS of CPEB4 NTD exhibits a LCST behavior, where droplets exist above T t ( 10 , 60 62 ) and previous studies have shown that LCST is driven by hydrophobic interactions and a dominant positive entropy term. 10 , 23 , 37 , 61 64 Moreover, Phe and Tyr have been predicted 65 and shown to play key role in the intermolecular interaction in LLPS, 5 , 37 , 11 , 15 , 61 , 66 , 67 which includes transient interactions via intermolecular charge−π and π–π interactions. We hypothesize that these hydrophobic and aromatic interactions can lead to entropy driven LLPS of CPEB4 NTD .…”
Section: Discussionmentioning
confidence: 99%
“…LLPS of CPEB4 NTD exhibits a LCST behavior, where droplets exist above T t ( 10 , 60 62 ) and previous studies have shown that LCST is driven by hydrophobic interactions and a dominant positive entropy term. 10 , 23 , 37 , 61 64 Moreover, Phe and Tyr have been predicted 65 and shown to play key role in the intermolecular interaction in LLPS, 5 , 37 , 11 , 15 , 61 , 66 , 67 which includes transient interactions via intermolecular charge−π and π–π interactions. We hypothesize that these hydrophobic and aromatic interactions can lead to entropy driven LLPS of CPEB4 NTD .…”
Section: Discussionmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR), enabled by site-directed spin labeling (SDSL), has received attention as a suitable technique that overcomes these limitations 61 . EPR spectroscopy is highly sensitive, requiring only small concentrations of spin label, and provides a precise measure of local dynamics via the rotational diffusion rate (typically on the order of 10 6 -10 9 Hz) of the radical nitroxyl spin label [62][63] .While the synthesis of stable spin-labeled molecules and technical data analysis previously precluded the implementation of EPR, recent developments in synthesis [64][65][66] and software [67][68] have made EPR accessible for investigating conformational dynamics. EPR has been used for measuring conformational dynamics on a self-assembled nanofibers composed of peptide amphiphiles (PAs).…”
Section: Conformational Dynamics In Supramolecular Systemsmentioning
confidence: 99%
“…The dynamic behavior of biomolecules and soft materials is often critical to their function (1)(2)(3)(4)(5). In protein biology, for instance, a dynamic picture of proteins has gradually replaced the purely structural ''lock-and-key'' model describing their function.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of fitting programs, challenges remain in the analysis of dynamics by CW-EPR. Expert analysis is typically necessary to reliably estimate fit uncertainty, as well to obtain self-consistent results in variable temperature experiments (4). Such analysis reduces the risk of overfitting and improves the reproducibility and consistency of fits.…”
Section: Introductionmentioning
confidence: 99%